Persistence of Antibody to Influenza A/H5N1 Vaccine Virus: Impact of AS03 Adjuvant - Chen, Wilbur H. (Clin Vaccine Immunol, 2016)
The adjuvant AS03 is stockpiled for future formulations with new and existing vaccines for the control of pandemic influenza virus. We previously reported the immunogenicity of an A/H5N1 vaccine extemporaneously mixed with the AS03 adjuvant for 42 days following vaccination. This report extends those findings to 1 year after vaccination.